Postoperative Recovery for Patients Undergoing Gynecologic Oncology Surgery [29Q]. (May 2016) - Filippi, Alexandra; Crnosija, Natalie; Dombroff, Marlo; Pearl, Michael L.
Abstract : INTRODUCTION: Our prospective cohort study examined gynecologic oncology surgery patients' self-assessed recovery post-discharge across multiple domains. We hypothesized that patients who undergo gynecological oncology surgery recover to their pre-operative baseline within 2 weeks of surgery. METHODS: This study was IRB-approved. All English-speaking patients over age 18 who underwent gynecology oncology surgery were offered the opportunity to participate. The PSR (Post-Discharge Surgical Recovery) survey was administered electronically via StudyTRAX. Patients completed a pre-surgery survey and matched daily surveys for 14 days post-surgery. The PSR score consists of 20 Likert scale-based survey question responses assessing factors of recovery, which were summed and calculated into a score. We performed Wilcoxon signed-rank test comparing pre-surgical scores to days 1, 7, 14 as well as the scores between days. Wilcoxon rank-sum tests evaluated day-specific PSR by covariates. RESULTS: Interim analysis of 250/500 patients demonstrated significant differences between PSR scores at pre-surgery and on days 1, 7, but not on day 14. Each of these days differed significantly from each other. There were no significant differences between ambulatory and admitted patients. CONCLUSION: Our preliminary results revealed that patients undergoing gynecologic oncology surgery rapidly regain function after surgery, approaching their self-assessed baseline by post-operative day 14. In recent years patients have been spending less time in the hospital post-operatively, placing most of their post-operative care in the community. Thus our results are reassuring given the trend towards earlier discharge. This study allowed each patient to report her own perceived recovery day by day as it was happening. The study is ongoing.